O-Linked N-Acetylglucosamine Modification of Mitochondrial Antiviral Signaling Protein Regulates Antiviral Signaling by Modulating Its Activity - Seo, Junghwa; Park, Yun Soo; Kweon, Tae Hyun; Kang, Jingu; Son, Seongjin; Kim, Han Byeol; Seo, Yu Ri; Kang, Min Jueng; Yi, Eugene C.; Lee, Yong-ho; Kim, Jin-Hong; Park, Boyoun; et al. (Frontiers in Immunology, 2021)
Post-translational modifications, including O-GlcNAcylation, play fundamental roles in modulating cellular events, including transcription, signal transduction, and immune signaling. Several molecular targets of O-GlcNAcylation associated with pathogen-induced innate immune responses have been identified; however, the direct regulatory mechanisms linking O-GlcNAcylation with antiviral RIG-I-like receptor signaling are not fully understood. In this study, we found that cellular levels of O-GlcNAcylation decline in response to infection with Sendai virus. We identified a heavily O-GlcNAcylated serine-rich region between amino acids 249–257 of the mitochondrial antiviral signaling protein (MAVS); modification at this site disrupts MAVS aggregation and prevents MAVS-mediated activation and signaling. O-GlcNAcylation of the serine-rich region of MAVS also suppresses its interaction with TRAF3; this prevents IRF3 activation and production of interferon-β. Taken together, these results suggest that O-GlcNAcylation of MAVS may be a master regulatory event that promotes host defense against RNA viruses.